Chronic Treatment with Clenbuterol Modulates Endothelial Progenitor Cells and Circulating Factors in a Murine Model of Cardiomyopathy - Rider, James E. (2009)
The purpose of this study was to determine the effects of chronic treatment with the beta 2 adrenergic receptor agonist clenbuterol on endothelial progenitor cells (EPC) in a well-characterized model of heart failure, the muscle LIM protein knockout (MLP(−/−)) mouse. MLP(−/−)mice were treated daily with clenbuterol (2 mg/kg) or saline subcutaneously for 6 weeks. Clenbuterol led to a 30% increase in CD31(+) cells in the bone marrow of MLP(−/−) heart failure mice (p<0.004). Clenbuterol did not improve ejection fraction. Clenbuterol treatment in MLP(−/−) mice was associated with significant changes in the following circulating factors: tissue inhibitor of metalloproteinase-type 1, leukemia inhibitory factor 1, C-reactive protein, apolipoprotein A1, fibroblast growth factor 2, serum glutamic oxaloacetic transaminase, macrophage-derived chemokine, and monocyte chemoattractant protein-3. Clen-buterol treatment in the MLP(−/−) model of heart failure did not rescue heart function, yet did increase CD31(+) cells in the bone marrow. This is the first evidence that a beta 2 agonist increases EPC proliferation in the bone marrow in a preclinical model of heart failure.